The use of TikTok as a Teaching Media to Teach Vocabulary of the Eight Grade Students at Junior High School - Lisa; Wisran; A. Musafir Rusyaidi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the effectiveness of the TikTok application in improving students’ English vocabulary skills and examines how TikTok supports vocabulary learning at SMP Negeri 7 Palopo. The study employed a quantitative pre-experimental method using a one-group pre-test and post-test design. The sample consisted of 22 eighth-grade students selected through cluster random sampling. The research instruments included vocabulary tests and questionnaires. The pre-test and post-test were administered to measure students’ vocabulary achievement before and after the treatment. The data were analyzed using descriptive statistics, a paired sample t-test, and the Wilcoxon signed-rank test. The findings revealed a significant improvement in students’ vocabulary after the implementation of TikTok-based learning. The mean score increased from 63.18 in the pre-test to 87.95 in the post-test, representing an improvement of approximately 39.2%. The paired sample t-test showed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between the pre-test and post-test score improvement, while only 2 students showed a decrease and 1 remained unchanged. The findings also indicated that TikTok supported vocabulary learning through audiovisual content, contextual examples, pronunciation, features, repetition, and interactive short videos that enhanced students’ engagement and vocabulary retention. Therefore, it can be concluded that TikTok is an effective learning tool for improving students’ vocabulary skills and supporting vocabulary learning in English language classrooms.